2017
DOI: 10.1159/000485139
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Randomized Controlled Trials on the Use of Suction Drains Following Rectal Surgery

Abstract: Background: Anastomotic leakage is one of the most feared complications of rectal resections. The role of drains in limiting this occurrence or facilitating its early recognition is still poorly defined. We aimed to study whether the presence of prophylactic pelvic drains affects the surgical outcomes of patients undergoing rectal surgery with extraperitoneal anastomosis. Methods: PubMed, EMBASE, and the Cochrane Library were systematically searched for randomized controlled trials comparing drained with undra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
0
28
0
2
Order By: Relevance
“…However, techniques to then subsequently reduce the leak rate have little evidence, including transanal decompression devices, intraluminal barriers or extraluminal devices such as tissue bolstering. The use of drains and mechanical bowel preparation also continues to be a subject of debate [8, 9]. …”
mentioning
confidence: 99%
“…However, techniques to then subsequently reduce the leak rate have little evidence, including transanal decompression devices, intraluminal barriers or extraluminal devices such as tissue bolstering. The use of drains and mechanical bowel preparation also continues to be a subject of debate [8, 9]. …”
mentioning
confidence: 99%
“…In the presence of recognized risk of bleeding or leak, there is relative consensus for their use. 8 Otherwise, the evidence supporting this is low. Recent meta-analyses of randomized control trials [8][9][10] in colorectal surgery have shown no benefit of prophylactically placed drains over no drain placement.…”
Section: Blame the Drain: Early Post-operative Small Bowel Obstructiomentioning
confidence: 99%
“…Recent meta-analyses of randomized control trials [8][9][10] in colorectal surgery have shown no benefit of prophylactically placed drains over no drain placement. Some studies 8,9 have suggested that their use is associated with a higher relative risk of post-operative bowel obstruction.…”
Section: Blame the Drain: Early Post-operative Small Bowel Obstructiomentioning
confidence: 99%
“…Emile & El-Hamed [1] reviewed seven systematic reviews and/or meta-analyses and concluded that level one evidence was against the use of pelvic drainage as a routine practice. Guerra et al [2] carried out a meta-analysis of four randomised controlled trials considered eligible for extraction of data and found no advantage in terms of anastomotic leak, pelvic complications, early intervention and mortality. However, the incidence of post-operative intestinal obstruction was significantly higher in the drained group.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Guerra et al . carried out a meta‐analysis of four randomised controlled trials considered eligible for extraction of data and found no advantage in terms of anastomotic leak, pelvic complications, early intervention and mortality. However, the incidence of post‐operative intestinal obstruction was significantly higher in the drained group.…”
mentioning
confidence: 99%